Self-powered multifunctional monitoring and analysis system based on dual-triboelectric nanogenerator and chitosan/activated carbon film humidity sensor. (April 2022) - Xu, Zhenyuan; Zhang, Dongzhi; Liu, Xiaohua; Yang, Yan; Wang, Xingwei; Xue, Qingzhong
Abstract: A humidity sensor driven by a dual-TENG has been developed for humidity detection at room temperature. In this work, we report a polymer humidity sensor with high response linearity. The sensitive material is made of chitosan (CS) and activated carbon (AC). The sensor is driven by a triboelectric nanogenerator based on fluorinated ethylene propylene copolymer (FEP). The CS/AC humidity sensitive film is coated on a PET substrate with a nickel-chromium alloy interdigitated electrode by spray technique. The peak-to-peak voltage of TENG can be close to 700 V, and the maximum output power is 12.208 mW. The output voltage of TENG is rectified to 48 V to power the humidity sensor, and then we realize that the voltage change range of the humidity sensor is between full voltage of 0–48 V through adjusting the resistance ratio and designing operational amplifier circuit. The sensor has a wide detection range (0%~97% RH) and good stability. Its response/recovery time under 33% RH and 97% RH conditions are 12 s/20 s and 22 s/21 s, respectively. The sensor can realize obvious identification of breathing characteristics in practical application tests. Meanwhile, the sensor can also be used to monitor the distance of the finger from the sensor surface and the response when the water column passes over the sensor surface. In addition, we also sent the signal of the humidity sensor to the smart terminal via WIFI module to monitor the signal changes caused by breathing and finger movement, and matlab was used to analyze the breathing data. Graphical Abstract: This figure shows the detailed structure of electricity generation part and the self-powered humidity detection system. ga1 Highlights: A flexible poly (fluorinated ethylene propylene) dual-triboelectric nanogenerator (TENG) was fabricated for the first time. A flexible chitosan/activated carbon composite sensor was integrated with the dual-TENG to form a self-powered humidity sensing system. The system demonstrates excellent humidity sensing properties and ultralow power consumption in a wide RH range.